Right ventriculo–pulmonary arterial uncoupling and poor outcomes in pulmonary arterial hypertension - Nakaya, Toshitaka (Pulm Circ, 2020)
Right ventricular function critically affects the prognosis of patients with pulmonary arterial hypertension. We aimed to analyze the prognostic value of right ventricular indices calculated using magnetic resonance imaging and right heart catheterization metrics in pulmonary arterial hypertension. We retrospectively collected data from 57 Japanese patients with pulmonary arterial hypertension and 18 controls and calculated six indices of right ventricular function: two indices of contractility (end-systolic elastance calculated with right ventricular maximum pressure and with magnetic resonance imaging metrics); two indices of right ventricular–pulmonary arterial coupling (end-systolic elastance/arterial elastance calculated with the pressure method (end-systolic elastance/arterial elastance (P)) and with the volume method (end-systolic elastance/arterial elastance (V)); and two indices of right ventricular diastolic function (stiffness (β) and end-diastolic elastance). We compared the indices between controls and patients with pulmonary arterial hypertension and examined their prognostic role. In patients with pulmonary arterial hypertension, end-systolic elastance (right ventricular maximum pressure) was higher (pulmonary arterial hypertension 0.94 (median) vs control 0.42 (mmHg/mL), p < 0.001), end-systolic elastance/arterial elastance (V) was lower (pulmonary arterial hypertension 0.72 vs control 1.69, p < 0.001), and β and end-diastolic elastance were significantly higher than those in the controls. According to the log-rank test, end-systolic elastance/arterial elastance (P) and end-diastolic elastance were significantly associated with the composite event rate. According to the multivariate Cox regression analysis, decreased end-systolic elastance/arterial elastance (P) was associated with a higher composite event rate (hazard ratio 11.510, 95% confidence interval: 1.954–67.808). In conclusion, an increased right ventricular contractility, diastolic dysfunction, and a trend of impaired right ventricular–pulmonary arterial coupling were observed in our pulmonary arterial hypertension cohort. According to the multivariate outcome analysis, a decreased end-systolic elastance/arterial elastance (P), suggestive of impaired right ventricular–pulmonary arterial coupling, best predicted the pulmonary arterial hypertension-related event.